Tindak Pidana Penyalahgunaan Aplikasi Bigo Live Terhadap Undang-Undang Nomor 19 Tahun 2016 tentang Informasi dan Transaksi Elektronik - Asheila Fahira A Assagaf; Afwan Faidzin; Syafrudin Makmur (JOURNAL of LEGAL RESEARCH, 2021)
ABSTRACTThe development of information technology today is very rapid with a variety of electronic information, namely social media. One of them is the Bigo Live Application. Bigo Live application itself is a Live Streaming application that is used as a place to disseminate pornographic content that is shown on social media for profit. Showing parts of the body that should not be exhibited and performing indecent acts. This is very inappropriate and can damage the morale of society, especially children.This study uses a juridical normative method, which uses written legal norms that are absolute based on the Act. Namely in the Law on Information and Electronic Transactions (ITE).The results of this study illustrate that the dissemination of pornographic content on social media on the Bigo Live application has fulfilled the elements of pornographic crime and has been regulated in Article 27 paragraph (1) Jo Article 45 paragraph (1) of Law Number 19 Year 2016 concerning Information and Transactions Electronics (ITE) and Article 4 paragraph (1) Jo Article 29 of Law Number 44 Year 2008 concerning Pornography.